23.6k views
1 vote
Simplify each expression. Select the correct answer from the drop-down menu.

−6(3i)(−2i) =


2(3 − i)(−2 + 4i) =

User Annel
by
5.3k points

2 Answers

5 votes

Answer:

Step-by-step explanation

-6(3i)(-2i)=-6(3i*-2i)=-6*-6i²=36i²

2(3-i)(-2+4i)=(6-2i)(-2+4i)=-12+24i+4i-8i²=-8i²+28i-12

User Lumpi
by
4.8k points
2 votes

Answer:

1. -36

2. -4+28i

3. 10+8i

Explanation:

EDGE2022

User EHB
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.